2012
DOI: 10.1111/mcn.12010
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in pregnancy and early childhood and associations with obesity in developing countries

Abstract: Concerns about the increasing rates of obesity in developing countries have led many policy makers to question the impacts of maternal and early child nutrition on risk of later obesity. The purposes of the review are to summarise the studies on the associations between nutrition during pregnancy and infant feeding practices with later obesity from childhood through adulthood and to identify potential ways for preventing obesity in developing countries. As few studies were identified in developing countries, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
149
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(171 citation statements)
references
References 85 publications
8
149
0
8
Order By: Relevance
“…[13][14][15] Some studies indicated increased birth weight by multivitamins might enhance the risk of obesity in adults. 16 In 2015 Dougan et al demonstrated that exposure to prenatal vitamins was not associated with body fatness either in childhood and adulthood. 17 In this study, we could find no association between iron supplementation and birth weight/macrosomia, although a combination of vitamin+iron lead to increased birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Some studies indicated increased birth weight by multivitamins might enhance the risk of obesity in adults. 16 In 2015 Dougan et al demonstrated that exposure to prenatal vitamins was not associated with body fatness either in childhood and adulthood. 17 In this study, we could find no association between iron supplementation and birth weight/macrosomia, although a combination of vitamin+iron lead to increased birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, breast-feeding and introduction of complementary foods adapted to both metabolic and nutritional requirements of growing infants are also envisioned as preventive measures against obesity later in life (5). Alteration of nutrition in a critical period of development in early life can affect the subsequent pattern of growth and development of tissues and organs and may predispose individuals to several disorders later in life (8,9).…”
mentioning
confidence: 99%
“…Optimal prenatal nutrition can reduce the risk of obesity in adults by influencing birth weight (5). Moreover, breast-feeding and introduction of complementary foods adapted to both metabolic and nutritional requirements of growing infants are also envisioned as preventive measures against obesity later in life (5).…”
mentioning
confidence: 99%
“…Food portion sizes; increased food consumption [47][48][49] High intake of total fat, saturated fat and trans fat [50,51] Fast food/Fried foods, [52][53][54][55] Junk food [56][57] -Soft drinks (sodas and sweetened beverages); -high caloric drinks,( sweetened & caffeinated beverages, juices, sugary drinks, juice blends); -Energy drinks [57][58][59][60][61] Alcoholic drinks [62] Overeating, binge eating, mindless eating and excessive snacking [56,62,63] Consumption of High fructose corn syrup and artificial sweeteners [55,59,[62][63][64] Insufficient dietary calcium intake or low dairy intake [67] Low intake of fiber , and Low intake of fruits and vegetables in foods [68,69] Not breastfeeding or short breastfeeding duration ; formula feeding instead of breastfeeding [70][71][72][73][74][75][76][77][78] Intestinal microbes [79][80][81][82][83] Antibiotics in human foods [84][85]…”
Section: Possible Dietary and Related Factors That Cause Obesity/overwementioning
confidence: 99%